The art of oocyte meiotic arrest regulation - Bo Pan; Julang Li (BMC, 2019)
Abstract A central dogma of mammalian reproductive biology is that the size of the primordial follicle pool represents reproductive capacity in females. The assembly of the primordial follicle starts after the primordial germ cells (PGCs)-derived oocyte releases from the synchronously dividing germline cysts. PGCs initiate meiosis during fetal development. However, after synapsis and recombination of homologous chromosomes, they arrest at the diplotene stage of the first meiotic prophase (MI). The diplotene-arrested oocyte, together with the surrounding of a single layer of flattened granulosa cells, forms a basic unit of the ovary, the primordial follicle. At the start of each estrous (animal) or menstrual cycle (human), in response to a surge of luteinizing hormone (LH) from the pituitary gland, a limited number of primordial follicles are triggered to develop into primary follicles, preantral follicles, antral follicles and reach to preovulatory follicle stage. During the transition from the preantral to antral stages, the enclosed oocyte gradually acquires the capacity to resume meiosis. Meiotic resumption from the prophase of MI is morphologically characterized by the dissolution of the oocyte nuclear envelope, which is generally termed the "germinal vesicle breakdown" (GVBD). Following GVBD and completion of MI, the oocyte enters meiosis II without an obvious S-phase and arrests at metaphase phase II (MII) until fertilization. The underlying mechanism of meiotic arrest has been widely explored in numerous studies. Many studies indicated that two cellular second messengers, cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) play an essential role in maintaining oocyte meiotic arrest. This review will discuss how these two cyclic nucleotides regulate oocyte maturation by blocking or initiating meiotic processes, and to provide an insight in future research.